Koncentracja cynku w glebach, w różnych odległościach od krawędzi jezdni na przykładzie drogi krajowej nr 3 w okolicach Nowego Miasteczka = Concetration of zinc at different distances from edge of road example national roads no 3 near Nowe Miasteczko - Walczak, Barbara; Chutko, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The results of zinc forms similar to the general and potentially available to plants at different distances, ranging from the edge of the road at the national road No. 3 in the area of Nowe Miasteczko. The aim of this study was determine the zinc content in the soil and evaluate the amount in relation to the standards.
Keywords: gleba; cynk; obszary przydrożne; soils; zinc; roadside areas